2018
DOI: 10.1177/1049909118775066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Time to Palliative Care Referrals in Patients With Small-Cell Lung Cancer: A Single-Centre Retrospective Review

Abstract: Palliative care treatment is a critical aspect in the oncological treatment of all patients diagnosed with advanced cancer, and this study highlights good compliance with existing national guidelines. Further research focusing on quality-of-life issues with the use of questionnaires to assess physical and psychological symptoms should be performed to further understand the impact of palliative care in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
1
1
Order By: Relevance
“…PC service data held by the Australian PC Outcomes Collaboration would have provided more accurate data; however, linkage was not available. In Stage IIIC–IV, the median time from diagnosis to PC was consistent with previous studies (Duggan et al, 2019; Watson et al, 2018). Those studies also had a shorter median time from first treatment to PC of 30 days, possibly due to treatment urgency associated with prognosis, symptom management, and performance status.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PC service data held by the Australian PC Outcomes Collaboration would have provided more accurate data; however, linkage was not available. In Stage IIIC–IV, the median time from diagnosis to PC was consistent with previous studies (Duggan et al, 2019; Watson et al, 2018). Those studies also had a shorter median time from first treatment to PC of 30 days, possibly due to treatment urgency associated with prognosis, symptom management, and performance status.…”
Section: Discussionsupporting
confidence: 90%
“…A previous literature review undertaken by the primary researcher (S.S) explored PC utilization and timing from diagnosis and death. PC utilization in the hospital setting varied between 14% (USA, Huo et al, 2021) and 100% (Ireland, Watson et al, 2018), whereas our study reported 54%. Community PC was lower in our cohort (15%) compared to Craigs et al (2018), who found greater utilization compared to hospital PC (45% vs. 40%).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation